Gangguan Sistem Pencernaan: Diare pada Balita Dengan Terapi Pemberian Oralit - Delima Ayu Sari; Fitri Afdhal; Ria Wulandari; Alvian Harisandy (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2026)
Background: Diarrhea is a condition of defecating more frequently than usual with a liquid stool texture accompanied by blood and mucus. Common causes of diarrhea come from contaminated food or water. Carried out to implement nursing care for patients with digestive system disorders: Diarrhea with hypovolemia problems. The purpose of this study is to describe the implementation of comprehensive nursing care for children diagnosed with diarrhea at Bhayangkara Mohamad Hasan Hospital, Palembang. Method: The study used a descriptive method with a case study approach and intervention of oral rehydration salts, subjects in case studies on both patients. Data collection techniques include interviews, observation, physical examination, and documentation. Results: In the assessment carried out on patient 1 with complaints of the patient saying defecating more than 3 times a day with a nursing diagnosis of hypovolemia, after 3 days of intervention of oral rehydration salts and implementation of SLKI and SIKI the problem was resolved. Conclusion: Oral rehydration salts are very effective for patients with fluid deficiency as a replacement for lost body fluids.